Cinnamaldehyde Inhibits the Function of Osteosarcoma by Suppressing the Wnt/β-Catenin and PI3K/Akt Signaling Pathways - Huang, Yanran (Drug Des Devel Ther, 2020)
BACKGROUND: Osteosarcoma (OS) is a primary bone tumor associated with locally aggressive growth and early metastatic potential that typically occurs in children and adolescents. Chinese traditional medicine Cinnamomum cassia Presl has been shown to have significant tumor-killing effect, in which cinnamaldehyde (CA) is the main active ingredient. PURPOSE: To explore the anticancer effect of CA on the osteosarcoma cells and the possible molecular mechanism. METHODS: Crystal violet assay, MTT assay and colony-forming assay were used to confirm the inhibitory role of CA in the proliferation of 143B and MG63 osteosarcoma cells. Hoechst 33258 staining and flow cytometry were used to observe apoptosis. The migration and invasion role of OS cells were evaluated using transwell assays and wound healing assays. Western blotting was used to analyse the protein expression levels. Nude mice were inoculated with 143B cells to establish an orthotopic OS tumor animal model and to investigate the effects of CA on OS tumors. RESULTS: According to crystal violet assay, MTT assay and colony-forming assay, CA significantly inhibited cell proliferation. Hoechst 33258 staining and flow cytometry analysis showed that CA-induced apoptosis in a concentration-dependent manner. In addition, transwell assays and wound healing assays showed that CA inhibited the migration and invasion of osteosarcoma cells. In vivo mouse models, CA inhibited the growth of osteosarcoma. The potential mechanisms could be that CA inhibited the transcriptional activity of Wnt/β-catenin and PI3K/Akt of the osteosarcoma. CONCLUSION: CA may inhibit the proliferation, migration, invasion and promote apoptosis of OS cells by inhibiting Wnt/β-catenin and PI3K/Akt signaling pathways. CA may be a potentially effective anti-tumor drug.